A content analysis of 12 episodes of the radio comedy-drama Toyang Ermitanya. - Bantiquete, Theola Hallares
This study is significant for it provides an in-depth treatment of the societal issues, thus, making people aware of the prevalent issues confronting the society at the same time. Second it serves as an important tool in analyzing the role of media in presenting various issues of the society in a manner that almost everyone can relate to. In the process, it will guide media practitioners in producing a satirical program that will catch the interest, and the same time, meet the need of the society in terms of information and entertainment.